2005
DOI: 10.1016/j.jacc.2004.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of mitral valve tenting in ischemic mitral regurgitation by transthoracic real-time three-dimensional echocardiography

Abstract: We clearly demonstrated 3D geometric deformity of the mitral leaflets and annulus in ischemic MR using novel software for creating images by 3D echocardiography. This technique will be helpful in making a proper decision for the surgical strategy in each patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
111
1
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(121 citation statements)
references
References 28 publications
5
111
1
4
Order By: Relevance
“…We have developed a novel software system, which allows us to visualize and quantify the complex geometry of the mitral valve [8]. By using the software, our group has reported the geometric changes in the mitral annulus and leaflets in functional MR. Mitral valve tenting with dilated annulus could be clearly demonstrated, and tenting volume and annular size were successfully measured three-dimensionally [8,[20][21][22][23]. We have also demonstrated that the 3D quantitation system was helpful in evaluating the effect of surgical procedure on 3D geometry of the mitral apparatus in patients with ischemic MR [24].…”
Section: Discussionmentioning
confidence: 95%
“…We have developed a novel software system, which allows us to visualize and quantify the complex geometry of the mitral valve [8]. By using the software, our group has reported the geometric changes in the mitral annulus and leaflets in functional MR. Mitral valve tenting with dilated annulus could be clearly demonstrated, and tenting volume and annular size were successfully measured three-dimensionally [8,[20][21][22][23]. We have also demonstrated that the 3D quantitation system was helpful in evaluating the effect of surgical procedure on 3D geometry of the mitral apparatus in patients with ischemic MR [24].…”
Section: Discussionmentioning
confidence: 95%
“…As in the case of prolapse, the likelihood of repair will be enhanced by having a versatile tool-kit of options, obviating the need for valve replacement. Detailed mapping of geometric substrates should allow us to tailor the ideal combination of annular, ventricular, and chordal approaches to achieve the best result in each patient [131,132]. Finally, the dynamics of ischemic MR indicate the need for continuing intensive heart failure therapy.…”
Section: Procedures To Chordaementioning
confidence: 99%
“…A number of mechanisms play role in the development of FMR. The suggested mechanisms for FMR in patients with left ventricular systolic dysfunction are the decrease in the transmitral pressure force which impairs effective mitral valve closure, the geometrical changes in the mitral annulus, papillary muscle, and mitral valve, and the dyssynchronic left ventricular and papillary muscle contractions (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…1). The mechanisms responsible are increased mitral tethering forces, reduction in closing forces and mechanical and electrical dyssynchrony (5)(6)(7)(8)(19)(20)(21). As the dilating heart becomes more spherical, the papillary muscles displaces outwards and towards the apex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation